Antibacterial activities of the methanol extracts, fractions and compounds from Harungana madagascariensis Lam. ex Poir. (Hypericaceae). (22nd August 2016) - Tankeo, Simplice B.; Damen, Francois; Sandjo, Louis P.; Celik, Ilhami; Tane, Pierre; Kuete, Victor
Abstract: Ethnopharmacological relevance: Harungana madagascariensis Lam. ex Poir. (Hypericaceae) is used in folk medicine to treat a variety of human ailments, mainly antibacterial, antifungal, antiviral and viral infections. In the present study, the methanol extract from the leaves (HML) and bark (HMB) of this plant as well as fractions (HMBa-c), sub-fractions (HMBa1-5) and compounds isolated from HMBa and HMBb namely betulinic acid (1 ), madagascin (2 ), ferruginin A (3 ) and Kaempferol-3- O-β -d -glucopyranoside (4 ) were tested for their antimicrobial activities against a panel of 28 g-negative bacteria including multidrug resistant (MDR) phenotypes. Materials and methods: The broth microdilution method was used to determine the minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of the above samples; column chromatography was used for the fractionation and purification of the bark extract whilst the chemical structures of compounds were determined using spectroscopic techniques. Results: Crude extract HMB together with fraction HMBa and sub-fraction HMBa3 were active on the 28 tested bacterial strains. HML as well as fractions HMBb, HMBc and sub-fractions HMBa1, HMBa2, HMBa4 and HMBa5 were selectively active. MIC values below or equal to 1024 µg/mL were recorded with these samples on 92.9% (for HML and HMBa 4), 82.1% (for HMBb), 78.6% (for HMBa2), 50.0% (for HMBa5) and 42.9% (for HMBc) tested bacteria. For crude material, the lowest MIC value below 8 µg/mL was obtained with HMB against Escherichia coli ATCC10536 and W3110 strains, and with sub-fraction HMBa3 against Klebsiella pneumoniae K2 strains. MIC values below 10 µg/mL were recorded with compound3 against E. coli ATCC10536, Enterobacter aerogenes ATCC13048 and EA294, Pseudomonas aeruginosa PA01, K. pneumoniae K2 and Kp55 and Enterobacter cloacae BM67. Conclusions: Harungana madagascariensis is a potential source of antimicrobial drugs to fight against MDR bacteria. The anthranol3 is the main antibacterial constituents of the bark of the plant. HMB and compound3 deserve further investigations to develop natural drug to combat Gram-negative bacteria and otherwise MDR phenotypes. Graphical abstract: The crude extracts from the bark (HMB) as well as fraction HMBa and sub-fraction HMBb were active on all the 28 tested bacterial strains. HMB had the lowest MIC value below 8 µg/mL against Escherichia coli ATCC10536 and W3110 strains whilst the corresponding value was obtained with HMBa3 against Klebsiella pneumoniae K2 strains. Betulinic acid (1 ), madagascin (2 ) and kaempferol 3- O-β -d -glucopyranoside (4 ) displayed selective activity. MIC below 10 µg/mL was recorded with ferruginin A (3 ) against E. coli ATCC10536, Enterobacter aerogenes ATCC13048 and EA294, Pseudomonas aeruginosa PA01, K. pneumoniae K2 and Kp55 and Enterobacter cloacae BM67.